Photocatalytic and antibacterial activities of green synthesized Ag doped MgO nanocomposites towards environmental sustainability. (June 2022) - Panchal, Priyanka; Paul, Devina Rattan; Gautam, Shubham; Meena, Poonam; Nehra, S.P.; Maken, Sanjeev; Sharma, Anshu
Abstract: The utilization of MgO nanoparticles (NPs) for Photocatalytic and antimicrobial activities has gained lots of attention in recent years. Since silver is an expensive material, it's of interest to check that doping of very small concentration of silver will increase the pollutant degradation efficiency of composites. Here Aloe Vera plant extract was used for synthesis of MgO, Ag NPs and Ag/MgO-nanocomposites (NCs). Green synthesized NPs and NCs were confirmed by using different techniques like UV–Vis, BET, TGA, FTIR, PL, XRD (optical, functional, Thermal, Structural) EDX, TEM, SEM, XPS, EIS and EPR (morphological, elemental, photoelectrical and ROS) studies respectively. Then NPs and NCs were applied for the photocatalytic activity of methylene blue (MB), phenol and antimicrobial studies of E. coli bacteria . Ag/MgO–NCs showed 90.18% dye and 80.67% phenol degradation in 120 min which killed E. Coli pathogenic bacteria in 25 min under solar light irradiations. In disk diffusion methods, it inactivates 24 mm area of bacterial cell growth. Thus, among these green synthesized NPs and NCs, Ag/MgO–NCs exhibited enhanced photocatalytic and antimicrobial activities. Graphical abstract: Image 1 Highlights: Ag doped MgO nanocomposites were synthesized with the help of Aloe Vera plant. These green synthesized nanocomposites were characterized by different techniques. These nanocomposites were investigated for photocatalytic and antimicrobial activities. Ag/MgO–NCs showed 90.18% dye and 80.67% phenol degradation in 120 min. Ag/MgO–NCs killed E. Coli pathogenic bacteria in 25 min under solar light irradiations.